EKSTRAK GETAH PEPAYA (Carica Papaya) DENGAN PENAMBAHAN Cu SEBAGAI DYE SENSITIZER SOLAR CELL (DSSC) - Kurniawidi, Dian Wijaya; Alaa, Siti; Rahayu, Susi (Indonesian Physical Review, 2018)
Indonesia is a biodiversity country. Abundance of biological resources may encourage researchers to optimize its use. As an example papaya trees are utilized as raw material for thin films. Sap of papaya latex is doppinged with Cu. This composition is depositioned on top of FTO by spin coating method. The addition of Cu dopping aims to control the rate of crystallinity of the material. This research will add Cu between 10% and 50% solution. Based on FTIR test results, flavonoid compounds might be obtained with O-H group, some aromatic rings C = C and C = O, aliphatic compounds C-H and -CO. Flavonoid compounds are potentially utilized as dye for DSSC. The thickness of dye produced by doping Cu 10% is approximately (0.5-2) Î¼m. Furthermore, dopping Cu from 20% to 40% can produce thickness around 10-50 nm. Meanwhile, the results of the XRD test show an effective Cu between 10% to 40%.